Experimental study on novel waste heat recovery system for sulfide-containing flue gas. (15th July 2021) - Ma, Hongqiang; Liang, Nuo; Liu, Yemin; Luo, Xinmei; Hou, Caiqin; Wang, Gang
Abstract: In order to further recover the waste heat from sulfide-containing flue gas, improve the recovery efficiency and reduce corrosion of heat exchanger before flue gas desulfurizer (FGD), a novel system based on the phase change heat transfer theory is proposed to recover the waste heat from sulfide-containing flue gas. The performance of novel waste heat recovery system is investigated by the experimental method. The results show that the heat recovery coefficient will increase with the heat load ratio while decrease with the circulation ratio. To ensure the high-efficiency operation of the novel system, the mass flow rate of lithium bromide solution should be adjusted in terms of the heat load ratio and circulation ratio in range of 48–178. Otherwise, it will be only adjusted in terms of the heat load ratio and increase with that. The exergy efficiency of the novel system will reduce with the heat load ratio because of the influence of energy efficiency of FGHE. But the exergy efficiency is about 25%–34% and lower. The heat transfer coefficient of FGHE is relatively higher for the heat load ratio in range of 0.7–1.1. The novel system is more advantageous in waste heat recovered from flue gas, the CO2 emission reduction and economic performance when the acid dew point temperature in range of 110–140 °C is changed under different operation conditions. The above conclusions will provide a theoretical basis for the operation of novel waste heat recovery system for sulfide-containing flue gas. Highlights: A novel waste heat recovery system is proposed for sulfur-containing flue gas. The experimental method is proposed to analyze the performance of novel system. Some measures are obtained to improve the performance of the novel system.